Double-layer stacking hole type SiO2-coated SiO2 core-shell microsphere as well as preparation method and application of double-layer stacking hole type SiO2-coated SiO2 core-shell microsphere
By constructing a porous shell structure with double or multiple pore size distributions on the surface of the SiO2 core, double-layer stacked pore SiO2@SiO2 core-shell microspheres are prepared, which solves the problem that the single pore size design in the existing technology cannot simultaneously and efficiently separate analytes of different sizes, realizes efficient and rapid separation of small molecules and large molecules, and reduces analysis cost and time.
Patent Information
- Application Number
- CN202510892164.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-30
- Publication Date
- 2025-09-19
AI Technical Summary
Existing core-shell microspheres generally adopt a single shell pore size design, which makes it difficult to simultaneously meet the requirements for efficient separation of analytes of different sizes, especially when dealing with sample systems with complex size distributions, resulting in poor separation effects.
A porous shell structure with dual or multiple pore size distribution is constructed on the surface of the SiO2 core. By integrating two or more pore sizes with significant differences, exclusive mass transfer paths are provided for small molecules and macromolecules. Double-layer stacked pore SiO2@SiO2 core-shell microspheres are prepared by the improved Stöber method, ultrasound-assisted sol-gel-hydrothermal pore expansion method and polymerization-induced colloidal coacervation method.
Significantly improve the selectivity and column efficiency of chromatographic separation, achieve efficient and rapid separation of small molecules and large molecules, reduce analysis cost and time, and eliminate the need for size fractionation pretreatment of samples of unknown molecular weight.
Smart Images

Figure CN120662259A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of chromatographic fillers, and particularly relates to double-layer stacked pore SiO2@SiO2 core-shell microspheres and a preparation method and application thereof. Background Art
[0002] Since the advent of the Halo core-shell column in 2006, this stationary phase consisting of a 1.7 μm non-porous SiO2 core and a 0.5 μm thick porous SiO2 shell has quickly become a research hotspot in the field of separation science due to its excellent chromatographic performance. Compared with traditional fully porous SiO2 stationary phases, the SiO2@SiO2 core-shell structure has significant advantages: the uniform particle size distribution and dense non-porous core make the eddy current diffusion coefficient ( A ), longitudinal diffusion coefficient ( B ) and mass transfer resistance coefficient ( C ) is significantly reduced, thereby optimizing mass transfer kinetics. Particularly noteworthy is that this 2.7 μm core-shell column achieves separation efficiencies comparable to sub-2 μm fully porous columns while simultaneously reducing column pressure to one-third to one-half of the latter, successfully resolving the technical challenge of traditional fully porous columns in balancing high-efficiency separations with low-pressure operation.
[0003] Based on these advantages, researchers have successfully developed a variety of synthetic methods, including layer-by-layer self-assembly, one-pot methods, template methods, template dissolution-induced redeposition methods, and two-phase methods, to prepare core-shell microspheres with diverse structures. However, existing core-shell microspheres generally use a single shell pore size design. While this can effectively improve column efficiency and separation speed, it is difficult to simultaneously meet the requirements for efficient separation of analytes of different sizes when processing sample systems with complex size distributions. Summary of the Invention
[0004] To address these issues, the present invention provides a double-layer stacked-pore SiO2@SiO2 core-shell microsphere, its preparation method, and application. This innovative design constructs a porous shell structure with dual or multiple pore size distributions on the SiO2 core surface. By integrating two or more pore sizes with significantly different sizes, this innovative design provides dedicated mass transfer pathways for solute molecules of varying sizes. This can provide dedicated mass transfer channels for both small and large molecules, significantly improving the selectivity and column efficiency of chromatographic separations. This provides a new solution for separating complex mixtures of varying sizes, significantly reducing analysis costs and time.
[0005] The present invention solves the above technical problems through the following technical solutions.
[0006] The first object of the present invention is to provide a double-layer stacked pore SiO2@SiO2 core-shell microsphere, wherein the core-shell microsphere has a micron-sized non-porous SiO2 as a core and a SiO2 nanoparticle stacking layer as a porous shell layer, wherein the porous shell layer includes a first SiO2 mesoporous shell layer and a second SiO2 mesoporous shell layer from the inside to the outside, the SiO2 nanoparticles in the first SiO2 mesoporous shell layer are stacked to form a first interstitial channel, and the SiO2 nanoparticles in the second SiO2 mesoporous shell layer are stacked to form a second interstitial channel, the first interstitial channel and the second interstitial channel are disordered and interconnected, the pore diameter of the first interstitial channel is 7 nm to 12 nm, and the pore diameter of the second interstitial channel is 30 nm to 50 nm.
[0007] Furthermore, the thickness of the first SiO2 mesoporous shell layer is 100 nm to 500 nm, and the thickness of the second SiO2 mesoporous shell layer is 100 nm to 300 nm.
[0008] Furthermore, the particle size of the micron-sized non-porous SiO2 is 2 μm to 3 μm.
[0009] A second object of the present invention is to provide a method for preparing the above-mentioned double-layer stacked porous SiO2@SiO2 core-shell microspheres, comprising the following steps: S1. Micron-sized non-porous SiO2 microspheres were prepared using the improved Stöber method.
[0010] S2. Using ethyl orthosilicate as a silicon source and dodecylamine as a template, a reaction system is formed. The reaction system is subjected to an ultrasound-assisted sol-gel-hydrothermal pore expansion method to deposit a first SiO2 mesoporous shell precursor on the surface of the micron-sized non-porous SiO2 microspheres. The first SiO2 mesoporous shell precursor is calcined for the first time to obtain a first SiO2 mesoporous shell, thereby forming SiO2@SiO2 core-shell microspheres.
[0011] S3. Use urea-based silane coupling agent to functionalize the first SiO2 mesoporous shell on the SiO2@SiO2 core-shell microspheres, then add urea, an aqueous solution of nano-SiO2 particles and a formaldehyde solution in sequence, and use the polymerization-induced colloidal coagulation method to coat the nano-SiO2 particles on the surface of the first mesoporous shell to obtain a second SiO2 mesoporous shell, forming a double-layer porous SiO2@SiO2 core-shell microsphere precursor.
[0012] S4. The double-layer porous SiO2@SiO2 core-shell microsphere precursor is calcined for the second time to melt and solidify the nano-SiO2 particles to obtain double-layer stacked porous SiO2@SiO2 core-shell microspheres.
[0013] Furthermore, the volume mass ratio of ethyl orthosilicate and dodecylamine template is 2 mL~12 mL:5 g~9 g. The ultrasound-assisted sol-gel-hydrothermal pore expansion method is to first subject the reaction system to ultrasonic treatment, then sol-gel at 20 ℃~40 ℃ for 1 h~6 h, and finally carry out hydrothermal pore expansion reaction at 120 ℃~180 ℃ for 6 h~12 h. The temperature of the first calcination is 650 ℃~750 ℃, and the time is 8 h~12 h.
[0014] Furthermore, the mass volume ratio of SiO2@SiO2 core-shell microspheres and urea-based silane coupling agent is 6 g: 3-8 mL, the temperature of the functionalization treatment is 60 ℃-90 ℃, and the time is 6 h-8 h.
[0015] Furthermore, the mass volume ratio of SiO2@SiO2 core-shell microspheres and nano-SiO2 particle aqueous solution is 1 g: 2~6 mL; the mass volume ratio of urea, nano-SiO2 particle aqueous solution and formaldehyde solution is 1 g~2 g: 1 mL~4 mL: 1.5 mL~3 mL.
[0016] Furthermore, during the polymerization-induced colloidal coagulation method, the pH of the solution is adjusted to 1.2-1.8, and the temperature of the second calcination is 600°C-700°C, and the time is 10 h-12 h.
[0017] The third object of the present invention is to provide the use of the above-mentioned double-layer stacked porous SiO2@SiO2 core-shell microspheres as filler in chromatographic separation.
[0018] Compared with the prior art, the present invention has the following beneficial effects: The double-layer stacked pore SiO2@SiO2 core-shell microspheres provided by the present invention construct a porous shell structure with a double or multiple pore size distribution on the surface of the SiO2 core, wherein micron-level non-porous SiO2 is used as the core, and then a mesoporous shell structure with a double or multiple pore size distribution is constructed on the surface of the micron-level non-porous SiO2 core, wherein the first SiO2 mesoporous shell is a disordered mesoporous shell with a smaller pore size, which mainly provides an action site for the separation of small molecule compounds, and the pore channels are disordered and are typical stacked pore channels. The second SiO2 mesoporous shell is a disordered mesoporous shell with a larger pore size, which is constructed with the first layer of disordered mesoporous shell with a smaller pore size as the base, and mainly provides an action site for the separation of large molecules, and its pore size is 30 nm to 50 nm. The core-shell stationary phase has a diameter of 100 nm and a pore size of 200 nm. The pores are composed of interstitial macropores formed by the accumulation of nano-SiO2 particles. The unique dual-pore channel provides exclusive mass transfer paths for analytes of different sizes, and can provide suitable mass transfer channels for small molecule compounds and macromolecules at the same time, thereby significantly improving the selectivity and column efficiency of chromatographic separation, and realizing efficient and rapid separation of small molecules and biomacromolecules. The differentiated shell pore structure and low column pressure enable the core-shell stationary phase to directly achieve efficient, rapid and low-cost separation without size fractionation pretreatment of samples with unknown molecular weight. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 Schematic diagram of the structure of the double-layer stacked porous SiO2@SiO2 core-shell microspheres of the present invention.
[0020] Figure 2 This is a flow chart of the preparation process of double-layer stacked porous SiO2@SiO2 core-shell microspheres of the present invention.
[0021] Figure 3 This is a morphology and structure diagram of micron-sized non-porous SiO2 microspheres according to Example 1 of the present invention. Figure 3 a is a scanning electron micrograph at a size of 2.5 μm, and b is a scanning electron micrograph at a size of 1 μm.
[0022] Figure 4 This is a morphology and structure diagram of SiO2@SiO2 core-shell microspheres in Example 1 of the present invention. Figure 4 a is a scanning electron microscopy at a size of 2.5 μm, b is a scanning electron microscopy at a size of 0.5 μm, c is a transmission electron microscopy at a size of 1 μm, d is a transmission electron microscopy at a size of 0.5 μm, e is a nitrogen adsorption-desorption curve, and f is a pore size distribution diagram.
[0023] Figure 5 This is a morphology and structure diagram of the double-layer stacked porous SiO2@SiO2 core-shell microspheres according to Example 1 of the present invention. Figure 5a is a scanning electron microscopy at a size of 2.5 μm, b is a scanning electron microscopy at a size of 1 μm, c is a transmission electron microscopy at a size of 2 μm, d is a transmission electron microscopy at a size of 0.5 μm, e is a nitrogen adsorption-desorption curve, and f is a pore size distribution diagram.
[0024] Figure 6 This is a column pressure-flow rate curve of the double-layer pore SiO2@SiO2-C18 core-shell column of the present invention.
[0025] Figure 7 This is a graph showing the reduced plate height-reduced flow rate curve of the double-layer porous SiO2@SiO2-C18 core-shell column for naphthalene.
[0026] Figure 8 This is the chromatographic separation diagram of the double-layer porous SiO2@SiO2-C18 core-shell column of the present invention for alkylbenzene and aromatic alcohol homologues. Figure 8 In figure a, the chromatographic separation diagram of six alkylbenzene homologues is shown, and in figure b, the chromatographic separation diagram of five aromatic alcohol homologues is shown.
[0027] Figure 9 This is the chromatographic separation diagram of the double-layer pore SiO2@SiO2-C18 core-shell column of the present invention for Bovine serum albumin hydrolysate and Ovalbumin hydrolysate. Figure 9 Figure a is the separation diagram of Bovine serum albumin enzymatic hydrolysate, and figure b is the separation diagram of Ovalbumin enzymatic hydrolysate.
[0028] Figure 10 This is the chromatographic separation diagram of 6 mixed proteins using the double-layer pore SiO2@SiO2-C18 core-shell column of the present invention. DETAILED DESCRIPTION
[0029] The following will provide a clear and complete description of the technical solutions in the embodiments of the present invention, in conjunction with the accompanying drawings. Obviously, the described embodiments are only a portion of the embodiments of the present invention, not all of them. All other embodiments derived by persons of ordinary skill in the art based on the embodiments of the present invention without inventive effort are also within the scope of protection of the present invention.
[0030] It should be noted that the professional terms used in the present invention are only for the purpose of describing specific embodiments, rather than limiting the scope of protection of the present invention. Certain words are used in the present invention to refer to specific components. Those skilled in the art should understand that technicians will use different nouns to refer to the same component. The present invention does not distinguish between components by the difference in nouns, but rather by the difference in the functions of the components. As mentioned throughout the specification and claims, "including" is an open term and should be understood as "including but not limited to".
[0031] The present invention provides a double-layer stacked pore type SiO2@SiO2 core-shell microsphere, such as Figure 1 As shown, the core-shell microspheres have micron-scale non-porous SiO2 as the core and a SiO2 nanoparticle accumulation layer as the porous shell, wherein the porous shell includes a first SiO2 mesoporous shell and a second SiO2 mesoporous shell from the inside to the outside, SiO2 nanoparticles in the first SiO2 mesoporous shell are accumulated to form a first interstitial channel, and SiO2 nanoparticles in the second SiO2 mesoporous shell are accumulated to form a second interstitial channel, the first interstitial channel and the second interstitial channel are disordered and interconnected, the pore size of the first interstitial channel is 7 nm to 12 nm, and the pore size of the second interstitial channel is 30 nm to 50 nm.
[0032] It should be noted that, in response to the problem that the existing single-pore core-shell stationary phase cannot be directly used for the rapid separation of mixtures with complex size distributions, the present invention designs a novel dual-pore SiO2@SiO2 core-shell microsphere stationary phase, wherein micron-scale non-porous SiO2 is used as the core, and then a mesoporous shell structure with a dual or multiple pore size distribution is constructed on the surface of the micron-scale non-porous SiO2 core, wherein the first SiO2 mesoporous shell is a disordered mesoporous shell with a smaller pore size, which mainly provides an action site for the separation of small molecule compounds, and the pores are disordered and are typical stacked pores. The second SiO2 mesoporous shell is constructed on the basis of the first SiO2 mesoporous shell, which is a disordered mesoporous shell with a larger pore size, which mainly provides an action site for the separation of large molecules, and its pore size is 30 nm to 50 nm. The core-shell stationary phase has a diameter of 100 nm and a pore size of 200 nm. The pores are composed of interstitial macropores formed by the accumulation of nano-SiO2 particles. The unique dual-pore channel provides exclusive mass transfer paths for analytes of different sizes, and can provide suitable mass transfer channels for small molecule compounds and macromolecules at the same time, thereby significantly improving the selectivity and column efficiency of chromatographic separation, and realizing efficient and rapid separation of small molecules and biomacromolecules. The differentiated shell pore structure and low column pressure enable the core-shell stationary phase to directly achieve efficient, rapid and low-cost separation without size fractionation pretreatment of samples with unknown molecular weight.
[0033] In addition, the double pores of the first SiO2 mesoporous shell and the second SiO2 mesoporous shell are completely separated in space, and the independently distributed structural characteristics can ensure that the solute molecules can diffuse from the surface of the core-shell microspheres to the interior of the pores through a relatively uniform mass transfer path, thereby effectively suppressing the chromatographic peak broadening phenomenon.
[0034] In some embodiments, the thickness of the first SiO 2 mesoporous shell layer is 100 nm to 500 nm, and the thickness of the second SiO 2 mesoporous shell layer is 100 nm to 300 nm.
[0035] It should be noted that the thickness of both SiO2 mesoporous shell layers in the present invention must be controlled within the range of 100 to 500 nm, and the total shell thickness must not exceed 800 nm. This design parameter was selected based on the following considerations: shell thickness directly affects key performance indicators of the chromatographic column, such as sample loading capacity, column efficiency, and separation speed. Therefore, the relationship between separation speed, column efficiency, and sample loading capacity must be balanced by optimizing the thickness of the two mesoporous shell layers.
[0036] In some embodiments, the particle size of the micron-sized non-porous SiO2 is 2 μm to 3 μm.
[0037] It should be noted that although reducing the particle size of the filler can improve the chromatographic column efficiency, it will also significantly increase the system pressure, and may even exceed the instrument's tolerance limit. When the core-shell filler particle size is less than 2 μm, three major problems will be faced: decreased filler uniformity, reduced column bed tightness, and deteriorated uniformity; it will also lead to uneven distribution of the mobile phase in the column cross section and aggravated temperature gradient effects, which in turn cause chromatographic peak broadening. Based on these limiting factors, current research on the particle size of core-shell microspheres mainly focuses on the sub-3 micron and sub-2 micron ranges. The present invention selects 2-3 μm non-porous SiO2 as the core material, among which sub-3 μm SiO2@SiO2 core-shell microspheres prepared with a particle size of about 2 μm are preferred, which maintains a lower column pressure characteristic while ensuring excellent column efficiency.
[0038] The second object of the present invention is to provide a method for preparing the above-mentioned double-layer stacked porous SiO2@SiO2 core-shell microspheres, such as Figure 2 As shown, the following steps are included: S1. Micron-sized non-porous SiO2 microspheres were prepared using the improved Stöber method.
[0039] S2. Using ethyl orthosilicate as a silicon source and dodecylamine as a template, a reaction system is formed. The reaction system is subjected to an ultrasound-assisted sol-gel-hydrothermal pore expansion method to deposit a first SiO2 mesoporous shell precursor on the surface of the micron-sized non-porous SiO2 microspheres. The first SiO2 mesoporous shell precursor is calcined for the first time to obtain a first SiO2 mesoporous shell, thereby forming SiO2@SiO2 core-shell microspheres.
[0040] S3. Use urea-based silane coupling agent to functionalize the first SiO2 mesoporous shell on the SiO2@SiO2 core-shell microspheres, then add urea, nano-SiO2 particle aqueous solution and formaldehyde solution in sequence, and use polymerization-induced colloidal coagulation method to coat the nano-SiO2 particles on the surface of the first mesoporous shell to obtain the second SiO2 mesoporous shell, forming a double-layer porous SiO2@SiO2 core-shell microsphere precursor.
[0041] S4. The double-layer porous SiO2@SiO2 core-shell microsphere precursor is calcined for the second time to melt and solidify the nano-SiO2 particles to obtain double-layer stacked porous SiO2@SiO2 core-shell microspheres.
[0042] It is worth noting that the present invention adopts two improved mesoporous shell preparation technologies: first, the improved ultrasound-assisted sol-gel method overcomes the problems of traditional methods that easily lead to agglomeration of core-shell microspheres and generation of secondary particles. The prepared stacked pore SiO2@SiO2 core-shell microspheres have the advantages of uniform shell and controllable pore size, and are particularly suitable as the substrate of the second layer of SiO2 mesoporous shell; second, the optimized polymerization-induced colloidal coagulation method uses SiO2 nanoparticles larger than 50 nm for deposition, which effectively solves the problems of uneven shell coating and poor reproducibility, while avoiding the blockage of the first shell layer pores during the deposition of the second shell layer.
[0043] In some embodiments, the volume mass ratio of tetraethyl orthosilicate and dodecylamine template is 2 mL to 12 mL: 5 to 9 g. The ultrasonic-assisted sol-gel-hydrothermal pore expansion method is to first subject the reaction system to ultrasonic treatment, then sol-gel at 20°C to 40°C for 1 h to 6 h, and finally conduct hydrothermal pore expansion reaction at 120°C to 180°C for 6 h to 12 h. The temperature of the first calcination is 650°C to 750°C, and the time is 8 h to 12 h.
[0044] In some embodiments, the mass volume ratio of SiO2@SiO2 core-shell microspheres and urea-based silane coupling agent is 6 g: 3-8 mL, the temperature of the functionalization treatment is 60°C-90°C, and the time is 6 h-8 h.
[0045] In some embodiments, the mass volume ratio of SiO2@SiO2 core-shell microspheres and nano-SiO2 particle aqueous solution is 1 g: 2-6 mL; the mass volume ratio of urea, nano-SiO2 particle aqueous solution and formaldehyde solution is 1 g-2 g: 1 mL-4 mL: 1.5 mL-3 mL.
[0046] In some embodiments, when the second SiO2 mesoporous shell layer is prepared by the polymerization-induced colloidal coagulation method, the process parameters are controlled as follows: the pH value of the reaction solution is adjusted to 1.2-1.8, the reaction temperature is maintained in the range of 15°C-30°C, and the reaction time is controlled in the range of 25 min-1.5 h; after the synthesis is completed, a second calcination treatment is required, the calcination temperature is set to 600°C-700°C, and the calcination time is 10 h-12 h.
[0047] The third object of the present invention is to provide the use of the above-mentioned double-layer stacked porous SiO2@SiO2 core-shell microspheres as filler in chromatographic separation.
[0048] The following is further described through specific examples.
[0049] Example 1 A double-layer stacked porous SiO2@SiO2 core-shell microsphere, wherein the core-shell microsphere has micron-scale non-porous SiO2 as the core and a SiO2 nanoparticle stacking layer as the porous shell. The porous shell includes, from the inside to the outside, a first SiO2 mesoporous shell layer and a second SiO2 mesoporous shell layer. The SiO2 nanoparticles in the first SiO2 mesoporous shell layer are stacked to form a first interstitial channel, and the SiO2 nanoparticles in the second SiO2 mesoporous shell layer are stacked to form a second interstitial channel.
[0050] The preparation method of the above-mentioned layer-stacked porous SiO2@SiO2 core-shell microspheres comprises the following steps: S1. Preparation of micron-sized non-porous SiO2 microspheres: Micron-sized non-porous SiO2 microspheres were prepared by the improved Stöber method, specifically: 500 mL of anhydrous ethanol was added to a 2000 mL three-necked flask, the temperature was raised to 30°C and stirred at 110 rpm, followed by the addition of 18 mL of KCl and 38 mL of ammonia water; a mixed solution of 80 mL of ethyl orthosilicate and 220 mL of ethanol was slowly dripped into the three-necked flask through a peristaltic pump, and the reaction was terminated after the particle size of the SiO2 core grew to the target size; after the reaction was completed, the ethanol mixed solution containing the SiO2 core was centrifuged and washed to remove incompletely hydrolyzed silicate oligomers, and finally the SiO2 core was washed with deionized water until neutral, and dried in an oven at 60°C to obtain micron-sized non-porous SiO2 microspheres.
[0051] S2. Preparation of the first SiO2 mesoporous shell layer: 7.4 g of dodecylamine and 3 g of the non-porous SiO2 microspheres obtained in S1 were weighed and ultrasonically dispersed in a mixed solution of 400 mL of anhydrous methanol and 100 mL of water to obtain solution A; 8 mL of ethyl orthosilicate was measured and added to solution A at a stirring speed of 300 rpm to obtain solution B. After stirring for 10 s, solution B was immediately transferred to an ultrasonic cleaner for treatment for 7 min; the reaction system was then placed in a 30 °C water bath and stirred at a speed of 150 rpm for 2 h. After the reaction was completed, solid-liquid separation was performed at a centrifugal speed of 2000 rpm to obtain core-shell microspheres, which were then hydrothermally expanded. The core-shell microspheres obtained by centrifugation were dispersed in 60 mL of deionized water and transferred to a 140 °C autoclave for heating for 6 h. After cooling, they were centrifuged and washed three times with anhydrous ethanol and then dried in a 60 °C oven for 6 h; finally, calcined at 10 °C·min -1 The dried core-shell microspheres were calcined in a muffle furnace at 700 ℃ for 10 h to obtain the first SiO2 mesoporous shell layer with a thickness of 400 nm and a pore diameter of 9.7 nm, forming SiO2@SiO2 core-shell microspheres.
[0052] S3, preparation of the second SiO2 mesoporous shell: 6 g of SiO2@SiO2 core-shell microspheres obtained by S2 were dispersed in 200 mL of 95% ethanol, and after adding 4.8 mL of γ-ureapropyltrimethoxysilane, stirred and refluxed in a 75 °C oil bath for 7 h for urea group modification. After the modification was completed, it was allowed to stand for 30 min, the supernatant was discarded, and the modified core-shell microspheres were obtained by filtration and washing 3 times with anhydrous ethanol and dried. 1 g of modified core-shell microspheres was dispersed in 120 mL of deionized water, and after ultrasonic treatment, 2 g of urea and 4 mL of an aqueous solution of 50 nm nano-SiO2 particles were added in turn. Use 6 molL -1 The pH of the reaction system was adjusted to 1.4 with hydrochloric acid, and 3 mL of 37% formaldehyde solution was added under stirring at 300 rpm. After stirring for 1 min, the speed was reduced to 80 rpm and the reaction was continued until the second shell reached the desired thickness. Ammonia and deionized water were added to terminate the reaction. After centrifugation, the product was washed with deionized water and ethanol three times each, dried, and spun at 10 °C min -1 The double-layer stacked porous SiO2@SiO2 core-shell microspheres were finally prepared by calcining at a heating rate of 650 ℃ for 10 h.
[0053] Example 2 A double-layer stacked porous SiO2@SiO2 core-shell microsphere, wherein the core-shell microsphere has micron-scale non-porous SiO2 as the core and a SiO2 nanoparticle stacking layer as the porous shell. The porous shell includes, from the inside to the outside, a first SiO2 mesoporous shell layer and a second SiO2 mesoporous shell layer. The SiO2 nanoparticles in the first SiO2 mesoporous shell layer are stacked to form a first interstitial channel, and the SiO2 nanoparticles in the second SiO2 mesoporous shell layer are stacked to form a second interstitial channel.
[0054] The preparation method of the above-mentioned layer-stacked porous SiO2@SiO2 core-shell microspheres comprises the following steps: S1. Preparation of micron-sized non-porous SiO2 microspheres: Micron-sized non-porous SiO2 microspheres were prepared by the improved Stöber method, specifically: 500 mL of anhydrous ethanol was added to a 2000 mL three-necked flask, the temperature was raised to 30°C and stirred at 110 rpm, followed by the addition of 18 mL of KCl and 38 mL of ammonia water; a mixed solution of 80 mL of ethyl orthosilicate and 220 mL of ethanol was slowly dripped into the three-necked flask through a peristaltic pump, and the reaction was terminated after the particle size of the SiO2 core grew to the target size; after the reaction was completed, the ethanol mixed solution containing the SiO2 core was centrifuged and washed to remove incompletely hydrolyzed silicate oligomers, and finally the SiO2 core was washed with deionized water until neutral, and dried in an oven at 60°C to obtain micron-sized non-porous SiO2 microspheres.
[0055] S2. Preparation of the first SiO2 mesoporous shell layer: 5 g of dodecylamine and 3 g of the non-porous SiO2 microspheres obtained in S1 were weighed and ultrasonically dispersed in a mixed solution of 400 mL of anhydrous methanol and 100 mL of water to obtain solution A; 2 mL of ethyl orthosilicate was measured and added to solution A at a stirring speed of 300 rpm to obtain solution B. After stirring for 10 s, solution B was immediately transferred to an ultrasonic cleaner for treatment for 7 min; the reaction system was then placed in a 20 °C water bath and stirred at a speed of 150 rpm for 1 h. After the reaction was completed, solid-liquid separation was performed at a centrifugal speed of 2000 rpm to obtain core-shell microspheres, which were then hydrothermally expanded. The core-shell microspheres obtained by centrifugation were dispersed in 60 mL of deionized water and transferred to a 120 °C autoclave for heating for 6 h. After cooling, they were centrifuged and washed three times with anhydrous ethanol and then dried in a 60 °C oven for 6 h; finally, calcined at 10 °C·min -1 The dried core-shell microspheres were calcined in a muffle furnace at 650 °C for 8 h to obtain the first SiO2 mesoporous shell layer and form SiO2@SiO2 core-shell microspheres.
[0056] S3, preparation of the second SiO2 mesoporous shell: 6 g of SiO2@SiO2 core-shell microspheres obtained by S2 were dispersed in 200 mL of 95% ethanol, and after adding 3 mL of γ-ureapropyltrimethoxysilane, stirred and refluxed in a 60 ° C oil bath for 8 h for urea group modification. After the modification is completed, let it stand for 30 minutes, discard the supernatant, filter and wash 3 times with anhydrous ethanol and dry to obtain modified core-shell microspheres. Disperse 1 g of modified core-shell microspheres in 120 mL of deionized water, and after ultrasonic treatment, add 1 g of urea and 1 mL of 50 nm nano-SiO2 particles in water. Use 6 molL -1 The pH of the reaction system was adjusted to 1.2 with hydrochloric acid, and 1.5 mL of 37% formaldehyde solution was added under stirring at 300 rpm. After stirring for 1 min, the speed was reduced to 80 rpm and the reaction was continued until the second shell reached the desired thickness. Ammonia and deionized water were added to terminate the reaction. After centrifugation, the product was washed with deionized water and ethanol three times each, dried, and spun at 10 °C min -1 The double-layer stacked porous SiO2@SiO2 core-shell microspheres were finally prepared by calcining at a heating rate of 600 ℃ for 10 h.
[0057] Example 3 A double-layer stacked porous SiO2@SiO2 core-shell microsphere, wherein the core-shell microsphere has micron-scale non-porous SiO2 as the core and a SiO2 nanoparticle stacking layer as the porous shell. The porous shell includes, from the inside to the outside, a first SiO2 mesoporous shell layer and a second SiO2 mesoporous shell layer. The SiO2 nanoparticles in the first SiO2 mesoporous shell layer are stacked to form a first interstitial channel, and the SiO2 nanoparticles in the second SiO2 mesoporous shell layer are stacked to form a second interstitial channel.
[0058] The preparation method of the above-mentioned layer-stacked porous SiO2@SiO2 core-shell microspheres comprises the following steps: S1. Preparation of micron-sized non-porous SiO2 microspheres: Micron-sized non-porous SiO2 microspheres were prepared by the improved Stöber method, specifically: 500 mL of anhydrous ethanol was added to a 2000 mL three-necked flask, the temperature was raised to 30°C and stirred at 110 rpm, followed by the addition of 18 mL of KCl and 38 mL of ammonia water; a mixed solution of 80 mL of ethyl orthosilicate and 220 mL of ethanol was slowly dripped into the three-necked flask through a peristaltic pump, and the reaction was terminated after the particle size of the SiO2 core grew to the target size; after the reaction was completed, the ethanol mixed solution containing the SiO2 core was centrifuged and washed to remove incompletely hydrolyzed silicate oligomers, and finally the SiO2 core was washed with deionized water until neutral, and dried in an oven at 60°C to obtain micron-sized non-porous SiO2 microspheres.
[0059] S2. Preparation of the first SiO2 mesoporous shell layer: 9 g of dodecylamine and 3 g of the non-porous SiO2 microspheres obtained in S1 were weighed and ultrasonically dispersed in a mixed solution of 400 mL of anhydrous methanol and 100 mL of water to obtain solution A; 12 mL of ethyl orthosilicate was measured and added to solution A at a stirring speed of 300 rpm to obtain solution B. After stirring for 10 s, solution B was immediately transferred to an ultrasonic cleaner for treatment for 7 min; the reaction system was then placed in a 40 °C water bath and stirred at a speed of 150 rpm for 6 h. After the reaction was completed, solid-liquid separation was performed at a centrifugal speed of 2000 rpm to obtain core-shell microspheres, which were then hydrothermally expanded. The core-shell microspheres obtained by centrifugation were dispersed in 60 mL of deionized water and transferred to a 180 °C autoclave for heating for 12 h. After cooling, they were centrifuged and washed three times with anhydrous ethanol and then dried in a 60 °C oven for 6 h; finally, calcined at 10 °C·min -1 The dried core-shell microspheres were calcined in a muffle furnace at 750 °C for 12 h to obtain the first SiO2 mesoporous shell layer and form SiO2@SiO2 core-shell microspheres.
[0060] S3, preparation of the second SiO2 mesoporous shell: 6 g of SiO2@SiO2 core-shell microspheres obtained by S2 were dispersed in 200 mL of 95% ethanol, and after adding 8 mL of γ-ureapropyltrimethoxysilane, stirred and refluxed in a 90 ° C oil bath for 6 h for urea group modification. After the modification is completed, let it stand for 30 minutes, discard the supernatant, filter and wash 3 times with anhydrous ethanol and dry to obtain modified core-shell microspheres. Disperse 1 g of modified core-shell microspheres in 120 mL of deionized water, and after ultrasonic treatment, add 2 g of urea and 6 mL of 50 nm nano-SiO2 particles in water. Use 6 molL -1 The pH of the reaction system was adjusted to 1.8 with hydrochloric acid, and 3 mL of 37% formaldehyde solution was added under stirring at 300 rpm. After stirring for 1 min, the speed was reduced to 80 rpm and the reaction was continued until the second shell reached the desired thickness. Ammonia and deionized water were added to terminate the reaction. After centrifugation, the product was washed with deionized water and ethanol three times each, dried, and spun at 10 °C min -1 The double-layer stacked porous SiO2@SiO2 core-shell microspheres were finally prepared by calcining at a heating rate of 700 ℃ for 12 h.
[0061] Since the dual-porous SiO2@SiO2 core-shell microspheres prepared in Examples 1 to 3 have similar structures and basically the same performance, the dual-porous SiO2@SiO2 core-shell microspheres prepared in Example 1 were taken as an example to test the structure and morphology of the double-layer stacked pore SiO2@SiO2 core-shell microspheres prepared in Example 1. The results are as follows: Figure 3 This is a morphology and structure diagram of micron-sized non-porous SiO2 microspheres according to Example 1 of the present invention. Figure 3 In the figure, a is a scanning electron microscope at a size of 2.5 μm, and b is a scanning electron microscope at a size of 1 μm. Figure 3 As shown in the figure, the particle size of the micron-sized non-porous SiO2 microspheres is about 2.4 μm.
[0062] Figure 4 This is a morphology and structure diagram of SiO2@SiO2 core-shell microspheres in Example 1 of the present invention. Figure 4 a is a scanning electron micrograph at 2.5 μm, b is a scanning electron micrograph at 0.5 μm, c is a transmission electron micrograph at 1 μm, d is a transmission electron micrograph at 0.5 μm, e is a nitrogen adsorption-desorption curve, and f is a pore size distribution diagram. Figure 4 As shown in Figure 1, the first SiO2 mesoporous shell was constructed on the micron-sized non-porous SiO2 microspheres. The thickness of the first SiO2 mesoporous shell was 400 nm and the pore diameter was 9.7 nm.
[0063] Figure 5 This is a morphology and structure diagram of the double-layer stacked porous SiO2@SiO2 core-shell microspheres according to Example 1 of the present invention. Figure 5 a is a scanning electron micrograph at 2.5 μm, b is a scanning electron micrograph at 1 μm, c is a transmission electron micrograph at 2 μm, d is a transmission electron micrograph at 0.5 μm, e is a nitrogen adsorption-desorption curve, and f is a pore size distribution diagram. Figure 5 The double-layer stacked porous SiO2@SiO2 core-shell microspheres successfully constructed two mesoporous shells with different pore sizes on the SiO2 core surface. The thickness of the second shell is approximately 180 nm. Surface area and pore size analysis revealed a bimodal pore size distribution, with the two pores approximately 10 nm and 30 nm in diameter, respectively.
[0064] The double-layer stacked porous SiO2@SiO2 core-shell microspheres prepared in Example 1 were used as stationary phase chromatography fillers for protein separation testing, including the following steps: 1 g of double-layer stacked porous SiO2@SiO2 core-shell microspheres prepared in Example 1 was dispersed in 40 mL of 6 molL -1 The mixture was stirred and refluxed in an oil bath at 120 °C for 6 h. After cooling, it was filtered through a G4 funnel and washed with deionized water until neutral. After drying at 125 °C for 10 h, it was ultrasonically dispersed with 1 mL of octadecyltrichlorosilane in 50 mL of dry toluene. The mixture was stirred and refluxed at 120 °C for 24 h to complete the C18 reverse phase modification. After the reaction, it was washed with toluene and anhydrous ethanol three times respectively. After vacuum drying at 60 °C overnight, it was tail-capped with trimethylchlorosilane to obtain a double-layer stacked porous SiO2@SiO2-C18 stationary phase.
[0065] 0.4 g of double-layer stacked porous SiO2@SiO2-C18 stationary phase was ultrasonically dispersed in 30 mL of isopropanol for 5 min and filled into a 50 mm×2.1 mm ID stainless steel column using an HPPS-20-400 column filling system at a pressure of 80 MPa using methanol and isopropanol (volume ratio of 1:1) as propellants for 40 min.
[0066] Permeability testing was performed using reverse phase chromatography using Waters' ACQUITY TM Ultra-high performance liquid chromatography (UPLC) was used, with ultrapure water as mobile phase A and chromatographically pure acetonitrile as mobile phase B, at a volume ratio of 20:80, at a flow rate of 0.1-1.0 mL·min -1 Perform pressure tests within a range of flow rates. Figure 6 The column pressure-flow rate curve of the double-layer pore SiO2@SiO2-C18 core-shell column of the present invention is shown in FIG. Figure 6 As shown in the figure, the column pressure of the core-shell column is low, and the column pressure shows a good linear relationship with the increase of the flow rate of the mobile phase. When the flow rate of the mobile phase is 1.0 mL·min -1The column pressure of the core-shell column was only 1870 psi, and its linear correlation coefficient R was 0.9999. These test results fully demonstrate that the core-shell column has a tightly packed stationary phase structure and excellent permeability.
[0067] Waters ACQUITY TM Ultra-high performance liquid chromatography (UPLC) was used. Mobile phase A was ultrapure water and mobile phase B was chromatographically pure acetonitrile in a volume ratio of 50:50. The detection wavelength was 254 nm, the injection volume was 1 μL, and the flow rate was between 0.1 and 1.0 mL min -1 Tests were performed within a range of flow rates. Figure 7 The graph of the reduced plate height-reduced flow rate of the double-layer porous SiO2@SiO2-C18 core-shell column for naphthalene is shown in FIG. Figure 7 As shown in the figure, when naphthalene is used as the test object for column efficiency analysis, the minimum equivalent plate height of the core-shell column for naphthalene is h min is 3.01.
[0068] Waters ACQUITY TM Ultra-high performance liquid chromatography (UPLC) was used in isocratic elution mode with ultrapure water as mobile phase A and chromatographic-grade acetonitrile as mobile phase B. The chromatographic conditions were set at a flow rate of 0.6 mL min -1 , detection wavelength of 254 nm, injection volume of 1 μL; a double-layer pore SiO2@SiO2-C18 core-shell column was used for the separation and analysis of alkylbenzene homologues and aromatic alcohol homologues. Figure 8 Figure 1 is a diagram of the separation and analysis of alkylbenzenes and aromatic alcohol homologues by the double-layer porous SiO2@SiO2-C18 core-shell column of the present invention. a is a diagram of the separation and analysis of 6 alkylbenzene homologues, and b is a diagram of the separation and analysis of 5 aromatic alcohol homologues. Figure 8 In a, the volume ratio of acetonitrile and water in the mobile phase is 70:30. Figure 8 In b, the volume ratio of acetonitrile and water in the mobile phase was 40:60, and the flow rate was 0.6 mL min -1 Detection wavelength: 254 nm; Figure 8 The chromatographic peaks are: 1-toluene, 2-ethylbenzene, 3-propylbenzene, 4-butylbenzene, 5-pentylbenzene, 6-hexylbenzene, 7-phenylethanol, 8-phenylpropanol, 9-phenylbutanol, 10-phenylpentanol, 11-phenylhexanol. Figure 8 As shown in Table 1, the core-shell reversed-phase column achieved baseline separation of six alkylbenzenes and five aromatic alcohol homologues within 2 min, with the theoretical plate number of p-hexylbenzene reaching 97,000·m -1 .
[0069] Table 1 Separation and analysis parameters of alkylbenzenes and aromatic alcohol homologues The peptide separation test was performed using Waters ACQUITY TM Ultra-high performance liquid chromatography (UPLC) was used. Mobile phase A was ultrapure water containing 0.1% trifluoroacetic acid, and mobile phase B was chromatographic grade acetonitrile containing 0.1% trifluoroacetic acid. A linear gradient elution program was used. The detection wavelength was 280 nm, the injection volume was 10 μL, and the flow rate was 0.6 mL min. -1 . Figure 9 This is a chromatographic separation analysis diagram of the double-layer pore SiO2@SiO2-C18 core-shell column of the present invention for Bovine serum albumin hydrolysate and Ovalbumin hydrolysate. Figure 9 Figure a is the separation and analysis diagram of Bovine serum albumin enzymatic hydrolysate, and figure b is the separation and analysis diagram of Ovalbumin enzymatic hydrolysate. Figure 9 For the separation and analysis of Bovine serum albumin hydrolysate, a linear gradient elution program was used to increase the mobile phase B from 10% to 25% and 100% at 0 min, 10 min and 14 min, respectively. For the separation and analysis of Ovalbumin hydrolysate, a linear gradient elution program was used to increase the mobile phase B from 10% to 25% and 100% at 0 min, 10 min and 14 min, respectively. Figure 9 As shown in the figure, after identification by UV detector, Bovine serum albumin hydrolysate can be separated into more than 30 components, and ovalbumin hydrolysate can be identified into nearly 40 components.
[0070] Waters ACQUITY TM Ultra-high performance liquid chromatography (UPLC) was used. Mobile phase A was ultrapure water containing 0.1% trifluoroacetic acid, and mobile phase B was chromatographically pure acetonitrile containing 0.1% trifluoroacetic acid. The protein concentration was 5 mg / mL. -1 A linear gradient elution program was used to increase mobile phase B from 10% to 60% within 2 min, with a detection wavelength of 280 nm, an injection volume of 10 μL, and a flow rate of 0.6 mL / min. -1 . Figure 10 This is the chromatographic separation diagram of 6 mixed proteins using the double-layer pore SiO2@SiO2-C18 core-shell column of the present invention. Figure 10 In the chromatographic peaks: 1 is Ribonuclease A, 2 is Insulin, 3 is Cytochrome C, 4 is Lysozyme, 5 is Bovine serum albumin, and 6 is Ovalbumin. Figure 10As shown in the figure, the double-layer pore SiO2@SiO2-C18 core-shell column can achieve complete separation of 6 proteins within 2 minutes.
[0071] In summary, the double-layer pore-type SiO2@SiO2-C18 core-shell column provided by the present invention can effectively achieve separation tasks that originally required two core-shell columns with different pore sizes. This feature significantly improves the efficiency and economy of chromatographic separation, and provides a new technical solution for the rapid separation and analysis of complex samples.
[0072] It should be noted that when numerical ranges are mentioned in the present invention, it should be understood that both endpoints of each numerical range and any value between the two endpoints may be selected. Since the steps and methods used are the same as those in the embodiments, in order to avoid redundancy, the present invention describes preferred embodiments. Although preferred embodiments of the present invention have been described, those skilled in the art may make additional changes and modifications to these embodiments once they understand the basic inventive concepts. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.
[0073] Obviously, those skilled in the art may make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if such changes and modifications fall within the scope of the claims and their equivalents, the present invention is intended to include such changes and modifications.
Claims
1. A double-layer stacked pore SiO2@SiO2 core-shell microsphere, characterized in that: The core-shell microspheres have micron-scale non-porous SiO2 as the core and a SiO2 nanoparticle accumulation layer as the porous shell layer, wherein the porous shell layer includes a first SiO2 mesoporous shell layer and a second SiO2 mesoporous shell layer from the inside to the outside, SiO2 nanoparticles in the first SiO2 mesoporous shell layer accumulate to form a first interstitial channel, and SiO2 nanoparticles in the second SiO2 mesoporous shell layer accumulate to form a second interstitial channel, the first interstitial channel and the second interstitial channel are disordered and interconnected, the pore diameter of the first interstitial channel is 7 nm to 12 nm, and the pore diameter of the second interstitial channel is 30 nm to 50 nm.
2. The double-layer stacked pore SiO2@SiO2 core-shell microspheres according to claim 1, characterized in that: The thickness of the first SiO2 mesoporous shell layer is 100 nm to 500 nm, and the thickness of the second SiO2 mesoporous shell layer is 100 nm to 300 nm.
3. The double-layer stacked pore-type SiO2@SiO2 core-shell microspheres according to claim 1, characterized in that: The particle size of micron-sized non-porous SiO2 is 2 μm to 3 μm.
4. A method for preparing double-layer stacked porous SiO2@SiO2 core-shell microspheres according to any one of claims 1 to 3, characterized in that: The following steps are involved: Micron-sized non-porous SiO2 microspheres were prepared by the improved Stöber method; Using tetraethyl orthosilicate as a silicon source, dodecylamine as a template, and a mixed solvent of methanol and water as a reaction solvent, the reaction system is subjected to an ultrasound-assisted sol-gel-hydrothermal pore expansion method to deposit a first SiO2 mesoporous shell precursor on the surface of the micron-sized non-porous SiO2 microspheres. The first SiO2 mesoporous shell precursor is subjected to a first calcination to obtain a first SiO2 mesoporous shell, thereby forming SiO2@SiO2 core-shell microspheres. The first SiO2 mesoporous shell of the SiO2@SiO2 core-shell microspheres was functionalized using a urea-based silane coupling agent. Urea, a 30 wt% aqueous solution of nano-SiO2 particles, and a formaldehyde solution were then added sequentially. The nano-SiO2 particles were coated on the surface of the first mesoporous shell using a polymerization-induced colloidal coagulation method to obtain a second SiO2 mesoporous shell, forming a double-layer stacked porous SiO2@SiO2 core-shell microsphere precursor. The double-layer stacked porous SiO2@SiO2 core-shell microsphere precursor is calcined for the second time to melt and solidify the nano-SiO2 particles to obtain double-layer stacked porous SiO2@SiO2 core-shell microspheres.
5. The method for preparing double-layer stacked pore SiO2@SiO2 core-shell microspheres according to claim 4, characterized in that: The volume mass ratio of ethyl orthosilicate and dodecylamine template is 2 mL~12 mL:5 g~9 g. The ultrasound-assisted sol-gel-hydrothermal pore expansion method is to first subject the reaction system to ultrasonic treatment, then sol-gel at 20℃~40℃ for 1 h~6 h, and finally carry out hydrothermal pore expansion reaction at 120℃~180℃ for 6 h~12 h. The temperature of the first calcination is 650℃~750℃, and the time is 8 h~12 h.
6. The method for preparing double-layer stacked pore SiO2@SiO2 core-shell microspheres according to claim 4, characterized in that: The mass volume ratio of SiO2@SiO2 core-shell microspheres and urea-based silane coupling agent was 6 g: 3-8 mL. The functionalization reaction was carried out in a 95% ethanol solvent system. The functionalization treatment temperature was 60 ℃-90 ℃ and the time was 6 h-8 h.
7. The method for preparing double-layer stacked pore SiO2@SiO2 core-shell microspheres according to claim 4, characterized in that: The mass-to-volume ratio of SiO2@SiO2 core-shell microspheres and nano-SiO2 particle aqueous solution is 1 g: 2-6 mL; the mass-to-volume ratio of urea, nano-SiO2 particle aqueous solution and formaldehyde solution is 1-2 g: 1-4 mL: 1.5-3 mL.
8. The method for preparing double-layer stacked pore SiO2@SiO2 core-shell microspheres according to claim 4, characterized in that: During the polymerization-induced colloidal coagulation method, the pH of the solution is adjusted to 1.2-1.8, and the temperature of the second calcination is 600° C.-700° C., and the time is 10 h-12 h.
9. Use of the double-layer stacked porous SiO2@SiO2 core-shell microspheres according to any one of claims 1 to 3 as a filler in chromatographic separation.
Citation Information
Cited By
Modified silicon dioxide chromatographic microspheres and preparation method thereof
CN122183564A
A modified silica chromatographic microsphere and its preparation method
CN122183564B